2020
DOI: 10.1016/j.ejca.2020.09.028
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis: the effect of active cancer treatment on severity of COVID-19

Abstract: Background The COVID-19 pandemic hit all over the world and cancer patients are more vulnerable for COVID-19. Mortality rate may increase up to 25% in solid malignancies. In parallel to increased mortality rates among cancer patients, safety concerns regarding cancer treatment has increased over time. However, there were contradictory results for the cancer treatment during pandemic. In this study, we assessed the effect of cancer treatment on the severity of COVID-19. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 60 publications
4
107
1
7
Order By: Relevance
“…A systematic review revealed that patients undergoing cancer treatment, such as chemotherapy, had a higher risk of death from COVID-19 [18] , which aligns with our own findings that patients who had received chemotherapy in the previous 30 days were more vulnerable to death from COVID-19. However, another systematic review found no association between the receipt of any type of cancer therapy and mortality from SARS-CoV-2 [14] .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A systematic review revealed that patients undergoing cancer treatment, such as chemotherapy, had a higher risk of death from COVID-19 [18] , which aligns with our own findings that patients who had received chemotherapy in the previous 30 days were more vulnerable to death from COVID-19. However, another systematic review found no association between the receipt of any type of cancer therapy and mortality from SARS-CoV-2 [14] .…”
Section: Discussionsupporting
confidence: 83%
“…Epidemiological and clinical evidence points to a greater risk of serious outcomes of COVID-19 in elderly patients, men, smokers, and patients with comorbidities such as hypertension, diabetes, obesity, and cancer [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] [See Text Box and Table 1 ]. Cancer patients are more vulnerable to complications and death when infected with SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 A recent meta-analysis including 16 studies concluded for an increased risk of death for chemotherapy administered within the last 30 days before COVID-19 diagnosis. 29 …”
Section: Discussionmentioning
confidence: 99%
“…The effect of the pandemic is disproportionate, the most affected being the countries with health systems that will become overburdened, with the risk of exacerbating socioeconomic inequalities. There is a consensus on the protection of patients and medical staff, the use of telemedicine services is recommended in the departments involved in the treatment of head and neck cancers, and an individualized decision should be taken after assessment of the benefit and risk of treatment, whether it is surgical followed by adjuvant treatment, or definitive radio-chemotherapy [9][10][11].…”
Section: Locally Advanced Head and Neck Cancer Treatment In Covid-19 mentioning
confidence: 99%